2015
DOI: 10.17516/1997-1370-2015-8-11-2408-2420
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Extracurricular Activities and Development of Personal and Interpersonal Skills in Adolescents

Abstract: In this study, we analyze self-reported development experience of adolescents involved in various

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
4
22
0
4
Order By: Relevance
“…Examples of CCAs or ECAs may include: general knowledge competition, essay writing competition, debating, drawing competition, various sports, diverse cultural programs, science exhibition, social awareness building, blood donation program, and so on. CCAs have received much attention from different researchers and academics across the world due to their positive effects on academic performance, various skills and personality development of the students (Ahmed, Rahman, Ali, Rahman, & Al-Azad, 2015;Bashir & Javed, 2012;Brandfon, 2018;Cariaga & Molina, 2016;Daniyal, Nawaz, Hassan, & Mubeen, 2012;Dhanmeher, 2014;Freeman, 2017;Ismail et al, 2016;Ivaniushina & Zapletina, 2015;Ivanova, Martins, & Kaftasev, 2017;Jamal, 2012;Kumar & Selvaraju, 2014;Le, 2013;Mehmood et al, 2012;Nghia, 2017;Prianto, 2016;Ritchie, 2018;Siddiky, 2019;Singh & Mishra, 2015;Villalobos et al, 2016). Mehmood et al (2012) found that CCAs have significant relationship with the development of such personality traits as self-confidence, honesty, adaptation, sociability, sympathetic attitude, social obligation and sense of responsibility among secondary school students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of CCAs or ECAs may include: general knowledge competition, essay writing competition, debating, drawing competition, various sports, diverse cultural programs, science exhibition, social awareness building, blood donation program, and so on. CCAs have received much attention from different researchers and academics across the world due to their positive effects on academic performance, various skills and personality development of the students (Ahmed, Rahman, Ali, Rahman, & Al-Azad, 2015;Bashir & Javed, 2012;Brandfon, 2018;Cariaga & Molina, 2016;Daniyal, Nawaz, Hassan, & Mubeen, 2012;Dhanmeher, 2014;Freeman, 2017;Ismail et al, 2016;Ivaniushina & Zapletina, 2015;Ivanova, Martins, & Kaftasev, 2017;Jamal, 2012;Kumar & Selvaraju, 2014;Le, 2013;Mehmood et al, 2012;Nghia, 2017;Prianto, 2016;Ritchie, 2018;Siddiky, 2019;Singh & Mishra, 2015;Villalobos et al, 2016). Mehmood et al (2012) found that CCAs have significant relationship with the development of such personality traits as self-confidence, honesty, adaptation, sociability, sympathetic attitude, social obligation and sense of responsibility among secondary school students.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Selvaraju (2014) observed that the students' participation in CCAs have a positive effect on their personality development taking into account seven dimensions involving appearance, verbal mannerism, gesticulation, mental alertness, stability of thoughts, leadership skills and self-confidence. Ivaniushina and Zapletina (2015) put forward that the ECAs have a positive effect on the development of personality and interpersonal skills of the Russian students. Singh and Mishra (2015) observed that participation in ECAs, in particular, yoga, horse-riding, sport activities, dance, music have positive effects on their academic performance of the students in the Government and Private Schools of India.…”
Section: Introductionmentioning
confidence: 99%
“…They are organized in order to help the students to gain a better understanding of the course and facilitate their different skill development tasks (Dhanmeher, 2014;Ingale, 2014;Siddiky, 2019). A number of studies have proposed that CCAs have effects on the development of personality and diverse soft skills of the students (Brandfon, 2018;Daniyal, Nawaz, Hassan, & Mubeen, 2012;Dhanmeher, 2014;Ismail et al, 2016;Ivaniushina & Zapletina, 2015;Ivanova, Martins, & Kaftasev, 2017;Kumar & Selvaraju, 2014;Jamal, 2012;Le, 2013;Mehmood, Hussain, Khalid, & Azam, 2012;Nghia, 2017;Prianto, 2016;Siddiky, 2019;Singh & Mishra, 2015;Villalobos et al, 2016). These activities are very important parts of educational institutions to develop the students' personality, morality, integrity and ethics, and strengthen the classroom learning (Ingale, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also it is purposed as a means to channeling the talents and interests of students as well as developing students as much as possible. The existence of extracurricular activities in schoolsis expected to be able to support the running of the learning process and also to shape the personality of students to become more mature, making students more willing to express something and be more creative in asking [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%